Visión Etnocentrista de los Estudiantes de la Escuela de Educación Básica “Nidia Jaramillo” Riobamba - Nieto Barahona., Diego Javier (2021)
The research entitled Ethnocentric Vision of the Students of the School of Basic Education "Nidia Jaramillo" of the Riobamba city, seeks to favor a change in the ethnocentric attitudes present in this group of students, taking into account that this problem involves the interaction between students, educators and educational context. This research aims to create a guide called "The School My Best Friend," where through methodological strategies, this kind of behavior can be counteracted within the students and solve this problem. This research is qualitative, of prospective typology, and a propositive level. It was considered that the sample would not be probabilistic, but an intentional sample and also a bibliographic investigation will be to carry out that will help discover transcendental information for this investigation. As a result of this guide, ten strategies are presented that seek to generate empathy in the students and tolerance towards other ethnic groups; it is hoped that this guide can be applied in different social contexts and manage to improve the school spaces' work environments. It is advisable to use this proposal in the teacher training processes to have a tool that helps in their work.